Regulation of cancer stem cell metabolism by secreted frizzled-related protein 4 (SFRP4) - Deshmukh, Abhijeet; Arfuso, Frank; Newsholme, Philip; Dharmarajan, Arunasalam (MDPI AG, 2018)
© 2018 by the authors. Licensee MDPI, Basel, Switzerland. Tumours contain a small number of treatment-resistant cancer stem cells (CSCs), and it is through these that tumour regrowth originates at secondary sites, thus rendering CSCs an attractive target for treatment. Cancer cells adapt cellular metabolism for aggressive proliferation. Tumour cells use less efficient glycolysis for the production of ATP and increasing tumour mass, instead of oxidative phosphorylation (OXPHOS). CSCs show distinct metabolic shift and, depending on the cancer type, can be highly glycolytic or OXPHOS dependent. Since Wnt signalling promotes glycolysis and tumour growth, we investigated the effect of the Wnt antagonist secreted frizzled-related protein 4 (sFRP4) on CSC metabolism. We demonstrate that sFRP4 has a prominent role in basal glucose uptake in CSCs derived from breast and prostate tumour cell lines. We show that sFRP4 treatment on CSCs isolated with variable glucose content induces metabolic reprogramming by relocating metabolic flux to glycolysis or OXPHOS. Altogether, sFRP4 treatment compromises cell proliferation and critically affects cell survival mechanisms such as viability, glucose transporters, pyruvate conversion, mammalian target of rapamycin, and induces CSC apoptosis under conditions of variable glucose content. Our findings provide the feasibility of using sFRP4 to inhibit CSC survival in order to induce metabolic reprogramming in vivo.